T cell-mediated elimination of cancer cells by blocking CEACAM6–CEACAM1 interaction. (1st January 2022) - Pinkert, Jessica; Boehm, Hans-Henning; Trautwein, Mark; Doecke, Wolf-Dietrich; Wessel, Florian; Ge, Yingzi; Gutierrez, Eva Maria; Carretero, Rafael; Freiberg, Christoph; Gritzan, Uwe; Luetke-Eversloh, Merlin; Golfier, Sven; et al.
ABSTRACT: Carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6), a cell surface receptor, is expressed on normal epithelial tissue and highly expressed in cancers of high unmet medical need, such as non-small cell lung, pancreatic, and colorectal cancer. CEACAM receptors undergo homo- and heterophilic interactions thereby regulating normal tissue homeostasis and angiogenesis, and in cancer, tumor invasion and metastasis. CEACAM6 expression on malignant plasma cells inhibits antitumor activity of T cells, and we hypothesize a similar function on epithelial cancer cells. The interactions between CEACAM6 and its suggested partner CEACAM1 on T cells were studied. A humanized CEACAM6-blocking antibody, BAY 1834942, was developed and characterized for its immunomodulating effects in co-culture experiments with T cells and solid cancer cells and in comparison to antibodies targeting the immune checkpoints programmed cell death protein 1 (PD-1), programmed death-ligand 1 (PD-L1), and T cell immunoglobulin mucin-3 (TIM-3). The immunosuppressive activity of CEACAM6 was mediated by binding to CEACAM1 expressed by activated tumor-specific T cells. BAY 1834942 increased cytokine secretion by T cells and T cell-mediated killing of cancer cells. The in vitro efficacy of BAY 1834942 correlated with the degree of CEACAM6 expression on cancer cells, suggesting potential in guiding patient selection. BAY 1834942 was equally or more efficacious compared to blockade of PD-L1, and at least an additive efficacy was observed in combination with anti-PD-1 or anti-TIM-3 antibodies, suggesting an efficacy independent of the PD-1/PD-L1 axis. In summary, CEACAM6 blockade by BAY 1834942 reactivates the antitumor response of T cells. This warrants clinical evaluation.